Increase of Public Debt and Budget Deficit and their Sustainability - Rica Ivan; Calin Tanase Ladar (Agora International Journal of Economical Sciences (AIJES), 2019)
Taking into account the need to ensure a standard of living adequate for citizens, by providing jobs, infrastructure, housing, etc., governments seek to allocate resources for that purpose, most often exceeding the ability to collect revenues to state budget and thus leading to accumulation of budget deficits and, implicitly, to increased public debt. Economic growth is the most important instrument for achieving the social and economic objectives of a central government. All these elements aforementioned intertwine with the external economic environment, the evolution thereof, while negative effects such as the economic crises have a contagious effect on the economy and society in general. After the economic and financial crisis of 2007, the public debts of the states increased, and the sustainability of the public finances has become a matter of major concern.
Keywords: 330